Desigualdade no acesso ao saneamento básico no Brasil: uma análise a partir das diferenças regionais e de situação do domicílio entre os anos de 2016 e 2022 - Custódio, Aline Maria Baldez (2023)
Access to drinking water and sanitation are human rights, recognized since 2010, directly related to health and quality of life, and the State must promote, protect and respect them, in order to guarantee their progressive realization. Despite this, basic sanitation is not expressly recognized in the Brazilian legal system as a social right, and inadequate situations or even lack of services still prevail for a considerable portion of the population, the result of a historical process of formation of our society and organization. of the sector. The present research aimed to analyze inequalities in access to water supply and sewage services due to regional differences and household situation in Brazil, throughout the historical series, between the years 2016 to 2022. To this end, data collected from secondary sources were used, by the National Sanitation Information System (Snis), the Continuous National Household Sample Survey (Pnad Contínua) and the Brazilian Atlas of Human Development. Data tabulation and analysis were carried out using Microsoft Excel using basic descriptive statistics and Pearson correlation analysis. The results confirm regional inequalities and by household situation, especially for people living in the North and Northeast and in rural areas. Among the services, sewage is the one with the biggest deficit. Furthermore, sanitation indicators have a strong or very strong relationship with indicators of infant mortality, per capita income and Human Development Index (HDI), which indicates that improving access to services is a relevant factor in improving quality of life. The relationships between water supply and sewage collection and between sewage collection and treatment are also strong. It is hoped that this research can contribute more elements to the debate, serving as a basis for future studies, as well as for the design of more assertive public policies to expand access to sanitation services for populations, especially those who need it most.